Aeneid : Book XII - Vergilius Maro, Publius (Cambridge Greek and Latin classics., 2013)
"Book XII brings Virgil's Aeneid to a close, as the long-delayed single combat between Aeneas and Turnus ends with Turnus' death - a finale that many readers find more unsettling than triumphant. In this, the first detailed single-volume commentary on the book in any language, Professor Tarrant explores Virgil's complex portrayal of the opposing champions, his use and transformation of earlier poetry (Homer's in particular) and his shaping of the narrative in its final phases. In addition to the linguistic and thematic commentary, the volume contains a substantial introduction that discusses the larger literary and historical issues raised by the poem's conclusion; other sections include accounts of Virgil's metre, later treatments of the book's events in art and music, and the transmission of the text. The edition is designed for upper-level undergraduates and graduate students and will also be of interest to scholars of Latin literature"--